Transformation, products, and pathways of chlorophenols via electro-enzymatic catalysis: How to control toxic intermediate products. (February 2016) - Du, Penghui; Zhao, He; Li, Haitao; Zhang, Di; Huang, Ching-Hua; Deng, Manfeng; Liu, Chenming; Cao, Hongbin
Abstract: Chlorophenols can be easily oxidized into chlorobenzoquinones (CBQs), which are highly toxic and have been linked to bladder cancer risk. Herein, we report the transformation, products, and pathways of 2, 4-dichlorophenol (DCP) by horseradish peroxidase (HRP) and electro-generated hydrogen peroxide (H2 O2 ) and suggest methods to control the formation of toxic intermediate products. After a 10-min electroenzymatic process, 99.7% DCP removal may be achieved under optimal conditions. A total of 16 reaction products, most of which are subsequently verified as DCP polymers and related quinone derivatives, are identified by using ultra-performance liquid chromatography-time-of-flight mass spectrometry (UPLC-TOF-MS). A five-step reaction pathway for DCP transformation, including HRP-driven substrate oxidation, substitution and radical coupling, quick redox equilibrium, nucleophilic reaction and precipitation from aqueous solution, is proposed. Current variations and the presence of CO2 could significantly affect these reaction pathways. In particular, higher currents enhance the hydroxylation process by promoting alkaline conditions and abundant H2 O2 formation. As both OH − and H2 O2 are strong nucleophiles, they easily react with CBQ products to form hydroxylated products, which can significantly reduce solution toxicity. An adequate supply of CO2 can provide favorable pH conditions and facilitate enzymatic steps, such as substrate oxidation and radical coupling, to generate precipitable polymerized products. All of the results suggest that toxic intermediate products can be effectively reduced and controlled during the electro-enzymatic process to remove DCP and other phenolic pollutants from wastewaters. Graphical abstract: Highlights: A detailed pathway map for DCP transformation in electro-enzymatic system is proposed. Higher current can particularly enhance dechlorination via hydroxylation steps. A controllable electro-enzymatic method is developed for DCP detoxification. Removal of DCP achieves 99.7% within 10 min of reaction at an optimal condition. CO2 may significant promote the enzymatic pathways by pH buffer effect.